Actuator fault reconstruction based on a robust adaptive observer. Issue 15 (1st October 2018) - Han, Zhiguo; Zhang, Ke; Liu, Haipeng
Abstract : A fault reconstruction method based on a robust adaptive observer is proposed to handle the actuator additive faults that exist in a non‐linear descriptor system that satisfies the Lipschitz conditions. First, a robust adaptive fault reconstruction observer is proposed. This method has the desired robust performance and can achieve accurate reconstructions of both abrupt and time‐varying faults in the presence of an external unknown disturbance. Then, to improve the transition process of fault reconstruction, an improved robust adaptive fault reconstruction observer is proposed. The improved robust adaptive fault reconstruction algorithm, which uses different coefficients for the proportion output errors and the derivative output errors, can enhance the rapidity and accuracy of fault reconstruction. The robust adaptive and improved robust adaptive observers are based on the linear matrix inequality technique. According to the Lyapunov stability theory, the stability conditions of the methods are derived. Additionally, the influence of an external unknown disturbance on the actuator fault reconstruction is suppressed using a robust method. Finally, two different examples are used to demonstrate the effectiveness of the proposed fault reconstruction methods.